Lessons learned for leaders: implications for parent-school communication in post-pandemic learning environments - Proff, Alexandria; Musalam, Rasha; Matar, Faten (Frontiers in Education, 2025)
IntroductionThe global COVID-19 pandemic resulted in 87% of students around the world being affected by school closures. This led to countries around the world implementing emergency plans to help mitigate the risks of exposure and spread of the virus. Schools mobilized resources and shifted to a new modality of instruction to assure the continuity of teaching and learning: online learning. There were numerous challenges for all stakeholders involved in this dynamic new learning space. At the forefront of these challenges was the involvement of, and communication with, parents regarding their child’s education at home. The pandemic presented schools with an opportunity to connect with families and strengthen collaboration. As communication is an integral component of collaboration, this study sought to ascertain the degree to which parent-school communication and parental involvement may have changed during and after the pandemic.MethodsA quantitative approach was employed to ascertain the views of parents of students in grade one through grade four attending private schools in the UAE. The researchers constructed a 30 item, Likert-style instrument which was subsequently validated for use and internal consistency assessed. The total number of responses was 479, which were analyzed using the Statistical Package for Social Sciences (SPSS). The researchers made use of an exploratory factor analysis and Wilcoxon signed-rank test to both explore parent perceptions during and after the pandemic.ResultsThese findings suggest that adjustments in communication strategies had a significant impact on how parents perceived their communication with schools. Our results indicate a significant shift in the accessibility and effectiveness of parent-school communication, suggesting that the pandemic triggered positive change in several aspects of educational communication. Parental involvement throughout and after the pandemic displayed a multifaceted pattern. Although parents became more attentive to their children’s academic success after the pandemic, there was a decrease in their total involvement in other educational activities.DiscussionThese mixed results suggest that while there was an overall trend of decreased parental involvement during and after the pandemic, individual variations exist, highlighting the need for school leaders to consider more nuanced approaches to facilitating and supporting parental involvement. Based on the results, the authors identified six suggestions for future practice to guide school leaders in fostering effective parent-school communication practices in post-Covid learning environments. Research concerning the impact COVID-19 has had on educational leaders’ interactions with parents is limited. Indeed, the degree to which parent-school communication and parental involvement have been successful during and after the pandemic has yet to be investigated. As such, this research aims to contribute to closing this gap in literature and provide school leaders and policymakers with practical suggestions for strengthening relationships between schools and families.